1999
DOI: 10.1159/000024174
|View full text |Cite
|
Sign up to set email alerts
|

Influx of Neutrophils into the Airway Lumen at 4 h after Segmental Allergen Challenge in Asthma

Abstract: Background: Segmental allergen challenge is a powerful tool to study inflammatory reactions in asthmatic airways. There is little information on the early events at 5 min and 4 h after allergen challenge with respect to the cell influx and the chemokine interleukin–8 (IL–8). Methods: Seven mild to moderate allergic asthmatics (AA group), 5 allergic nonasthmatics (ANA group) and 5 nonallergic controls underwent segmental allergen challenge, with allergen doses based upon skin reactivity. Bronchoalveolar lavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 21 publications
5
58
0
Order By: Relevance
“…During this phase, only the higher dose of S-CMC appeared effective. In asthma patients [27,28] and in animal models [15], neutrophils have been shown to be the first inflammatory cells in the airways after allergen challenge. Neutrophils are known to release several chemical mediators known to be toxic to the airways.…”
Section: Cytokine Levels In Cultured Cellsmentioning
confidence: 99%
“…During this phase, only the higher dose of S-CMC appeared effective. In asthma patients [27,28] and in animal models [15], neutrophils have been shown to be the first inflammatory cells in the airways after allergen challenge. Neutrophils are known to release several chemical mediators known to be toxic to the airways.…”
Section: Cytokine Levels In Cultured Cellsmentioning
confidence: 99%
“…Recruitment of neutrophils into the lungs is commonly seen in asthma and animal models of lung allergy (1)(2)(3)(4)(5). Mechanisms to explain increased neutrophil infiltration in asthma and allergy are not well characterized.…”
Section: Ag-specific Activation Of Cd4 ϩ T Cells As a Mechanism For Cmentioning
confidence: 99%
“…Consequently, it will be useful to understand the mechanisms explaining up-regulation of chemokines in lung allergy. It has recently been shown that segmental allergen challenge in allergic asthmatics rapidly induced neutrophil chemokine production and neutrophil influx (3). In that study, although neutrophil chemokine production was thought to be mast cell independent, the underlying mechanism was unclear.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…CCL11/eotaxin [6]), is broadly accepted as critical to the eosinophil response. However, CXCL8/interleukin (IL)-8 is also strongly expressed within allergic lesions [7][8][9][10] and eosinophils are responsive to this CXCR1/CXCR2 ligand [11,12]. Indeed, the decreased eosinophilia after allergen immunotherapy may be related to reduced CXCL8/IL-8 responses to allergen challenge [13].…”
mentioning
confidence: 99%